A food chain model with prey-taxis and chemotaxis. (1st January 2013) - Ma, Manjun; Han, Yazhou; Tao, Jicheng; Wu, Delin
From the dynamic point of view we construct a food chain model with chemotaxis and investigate theoretically and numerically its steady states. Our results show how the combined action of the death rates, chemotaxis, diffusivity and predator-prey interactions influence the survival ability of multiple consumer levels in a closed ecological system with self-produced nutriment. Furthermore, the food chain length of our model can be determined by the coexistence conditions of all consumer levels. The analytical results are corroborated by numerical simulations.